Web Information Systems Engineering - WISE 2009 10th International Conference, Poznen, Poland, October 5-7, 2009, Proceedings - Vossen, Gottfried; Long, Darrell D. E.; Xu Yu, Jeffrey (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This book constitutes the proceedings of the 10th International Conference on Web Information Systems Engineering, WISE 2009, held in Poznan, Poland, in October 2009. The 33 revised full papers and 17 revised short papers presented together with two keynote talks were carefully reviewed and selected from around 144 submissions. The papers are organized in topical sections on web computing, industrial session, tagging, semantics, search, visualization, web services, trust and uncertainty, recommendation and quality of service, user interfaces, web understanding, exploiting structures information on the web, systems, data mining and querying, querying and workflow and architecture.